Penggunaan Media Sosial dan Dukungan Keluarga sebagai Faktor yang Berkontribusi dalam Perilaku Seksual Berisiko pada Remaja Putra di SMKN X Kota Tarakan - Vinny Alvionita; Andi Sri Hastuti Handayani Usman; Rizky Vaira; Shela Kurnia Sukma Wati (Journal Scientific of Mandalika (JSM) e-ISSN 2745-5955 | p-ISSN 2809-0543, 2025)
This study aims to analyze the relationship between individual factors, namely knowledge factors and social media use factors, as well as family factors, namely adolescent residential status and parents' marital status with risky sexual behavior in young men. This research uses an analytical observational design with a cross-sectional approach. The number of respondents was 112 young men at SMKN X Tarakan City. Data analysis was carried out univariate and bivariate using the Prevalence Odds Ratio (POR) test. Most respondents were 16 years old (43.8%). The majority of respondents had good knowledge about sexual behavior (86.6%), high use of social media (83.9%), lived with their parents (95.5%), and had parents with complete marital status (84.8%). As many as 68.7% of respondents had risky sexual behavior. The use of social media is associated with risky sexual behavior (POR = 2.615), all respondents with their own residence status (4.5%) have risky sexual behavior, and the marital status of divorced parents also increases the incidence of risky sexual behavior (POR = 2.379). It is necessary to strengthen sexuality education which does not only focus on increasing knowledge, but also on controlling the use of social media, parental involvement needs to be increased through supervision, open communication and emotional support, especially for teenagers who live alone or come from families with divorced parents, in order to prevent risky sexual behavior